Cluster Component of Sustainable Regional Development: Romanian Practice and Ukrainian Realities - Liashenko, V.; Trushkina, N. (Економічний вісник Донбасу, 2021)
At present, the problems of improving the management of cluster structures in the economic regions of Ukraine, taking into account the best Romanian experience in accordance with modern challenges related to smart specialization, modernization of production and digitalization of organizational and managerial processes, are especially relevant.
For the further development of clusters in Romania it is necessary to develop a set of measures, namely: stimulating exports through internationalization; formation of fundamentally new value chains integrated into vertical industries; business strategy; assistance in financing innovative projects for technology transfer based on the mechanism of public-private partnership and with the involvement of private investment; use of cluster management tools; developing tools that can support efficient resource allocation processes among cluster members; training; formation of proper organizational culture. The implementation of these measures should be carried out with the help of the European Cluster Cooperation Platform and the European Cluster Improvement Program, the EU Action “Cluster Go International”, and the Eurocluster Program for the period 2021-2027.
Based on the generalization of the best Romanian experience, it is established that in order to increase the competitiveness of national and regional economies, it is necessary to create cluster structures as effective forms of partnership. However, the study revealed that the current legislation of Ukraine does not pay due attention to the formation and functioning of clusters. To do this, it is necessary to make changes and additions to the Concept of creating clusters in Ukraine, Regional Development Strategies until 2027, and Action Plans for their implementation for 2021-2023 to create cluster structures as a business entity. It is expedient to develop and approve the Concepts of cluster policy and the Target Program “Formation and development of clusters in the regions of Ukraine for 2021-2023”, which should provide for the creation of clusters as a special type of enterprise association in various fields and taking into account regional specifics. Для подальшого розвитку кластерних утворень у Румунії необхідно розробити комплекс заходів, а саме: стимулювання експорту шляхом інтернаціоналізації; формування принципово нових ланцюгів доданої вартості, інтегрованих у вертикальні галузі; стратегування діяльності; сприяння фінансуванню інноваційних проєктів для передачі технологій на основі механізму публічно-приватного партнерства та із залученням приватних інвестицій; використання інструментів кластерного менеджменту; розроблення інструментарію, який може підтримувати ефективні процеси розподілу ресурсів між учасниками кластеру; підготовка кадрів; формування належної організаційної культури. Реалізація перелічених заходів має здійснюватися за допомогою Європейської платформи кластерного співробітництва та у рамках Європейської програми удосконалення кластерів, Акції ЄС «Cluster Go International», Програми єврокластерів на період 2021-2027 роки.
На підставі узагальнення передового румунського досвіду встановлено, що для підвищення конкурентоспроможності національної й регіональної економік необхідно створювати кластерні структури як ефективні форми партнерства. Але у результаті дослідження виявлено, що в чинному законодавстві України не приділяється належної уваги формуванню й функціонуванню кластерів. Для цього необхідно внести зміни і доповнення до Концепції створення кластерів в Україні, Стратегій регіонального розвитку до 2027 року і Планів заходів з їх реалізації на 2021-2023 роки щодо створення кластерних структур як суб’єкта господарювання. Доцільним є розроблення та схвалення Концепцій кластерної політики та Цільової програми «Формування та розвиток кластерних утворень у регіонах України на 2021-2023 роки», у яких необхідно передбачити створення кластерів як особливого виду об’єднань підприємств у різних сферах діяльності та з урахуванням регіональної специфіки. В настоящее время особую актуальность приобретают проблемы совершенствования управления развитием кластерных структур в экономических районах Украины с учётом передового румынского опыта в соответствии с современными вызовами, связанными со смарт-специализацией, модернизацией производства и цифровизацией организационных и управленческих процессов.
Для дальнейшего развития кластерных образований в Румынии необходимо разработать комплекс мероприятий, а именно: стимулирование экспорта путём интернационализации; формирование принципиально новых цепей добавленной стоимости, интегрированных в вертикальные отрасли; стратегирование деятельности; содействие финансированию инновационных проектов для передачи технологий на основе механизма публично-частного партнёрства и с привлечением частных инвестиций; использование инструментов кластерного менеджмента; разработка инструментария, который может поддерживать эффективные процессы распределения ресурсов между участниками кластера; подготовка кадров; формирование организационной культуры. Реализация перечисленных мероприятий должна осуществляться с помощью Европейской платформы кластерного сотрудничества и в рамках Европейской программы совершенствования кластеров, Акции ЕС «Cluster Go International», Программы еврокластеров на период 2021-2027 годы.
На основании обобщения передового румынского опыта установлено, что для повышения конкурентоспособности национальной и региональной экономики необходимо создавать кластерные структуры как эффективные формы партнёрства. Но в результате исследования обнаружено, что в действующем законодательстве Украины не уделяется должного внимания формированию и функционированию кластеров. Для этого необходимо внести изменения и дополнения в Концепцию создания кластеров в Украине, Стратегии регионального развития до 2027 года и Планы мероприятий по их реализации на 2021-2023 годы по созданию кластерных структур как субъекта хозяйствования. Целесообразно разработать Концепцию кластерной политики и Целевую программу «Формирование и развитие кластерных образований в регионах Украины на 2021-2023 годы», в которых необходимо предусмотреть создание кластеров как особого вида объединений предприятий в различных сферах деятельности и с учётом региональной специфики.